2013
DOI: 10.1002/nau.22525
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation of the conus medullaris for refractory pudendal neuralgia: A prospective study of 27 consecutive cases

Abstract: Spinal cord stimulation of the conus medullaris is a safe and effective technique for long-term treatment of refractory pudendal neuralgia. Routine use of this technique, which has never been previously reported in the literature in this type of patient, must now be validated by a larger scale study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 16 publications
0
40
0
2
Order By: Relevance
“…The distribution of the DNP explains our patient's symptoms and why he experienced anterior penile pain during micturition (due to anterior possibility of microscopic damage rostral to this level cannot be fully excluded, we believe that the majority of DNP fibers terminate in the dorsal horn of the adult human conus medullaris at levels corresponding to the middle of the T12/L1 disc and the rostral half of the L1-vertebral body. Indirect corroboration of our hypothesis comes from two studies whereby the epidural stimulation of the conus medullaris was carried out to control refractory pudendal neuralgia [15,16]. In both studies, stimulation via epidural leads were placed at the level of the T12-L1 vertebral bodies resulted in significant improvements in pudendal neuralgia.…”
Section: Discussionmentioning
confidence: 62%
“…The distribution of the DNP explains our patient's symptoms and why he experienced anterior penile pain during micturition (due to anterior possibility of microscopic damage rostral to this level cannot be fully excluded, we believe that the majority of DNP fibers terminate in the dorsal horn of the adult human conus medullaris at levels corresponding to the middle of the T12/L1 disc and the rostral half of the L1-vertebral body. Indirect corroboration of our hypothesis comes from two studies whereby the epidural stimulation of the conus medullaris was carried out to control refractory pudendal neuralgia [15,16]. In both studies, stimulation via epidural leads were placed at the level of the T12-L1 vertebral bodies resulted in significant improvements in pudendal neuralgia.…”
Section: Discussionmentioning
confidence: 62%
“…We identified two studies of targeted conus medullaris stimulation (CMS) that fit our selection criteria. Buffenoir et al reported on a prospective study of 27 patients treated with SCS directed to the conus medullaris (SCS‐CM) for refractory pudendal neuralgia. Kapural et al published a retrospective case‐series of six female patients treated with SCS‐CM for severe intractable visceral pelvic pain (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified six studies of targeted dorsal root ganglion stimulation (SCS-DRG) that satisfied our selection criteria. Of these six studies, five were prospective observational studies, with two studies by the same authors detailing the same patient population at 6 and 12 month follow-up (44)(45)(46)(47)(48)(49)(50). We identified one retrospective chart review (Table 3) (49).…”
Section: Resultsmentioning
confidence: 99%
“…However, treatment of pain in the perineum with SCS‐induced paresthesias has long been recognized as a clinical challenge . The clinician is confronted with multiple lead placement options, including retrograde sacral nerve root stimulation (SNRS), transforaminal lead placement for SNRS, anterograde caudal SNRS, midthoracic lead placement (T6 level), and thoracolumbar junction lead placement …”
Section: Introductionmentioning
confidence: 99%